A multiple case study on the inter‐group interaction speed in large, embedded software companies employing agile. Issue 1 (7th December 2015) - Martini, Antonio; Pareto, Lars; Bosch, Jan
Abstract: The adoption of Agile Software Development in large companies is a recent phenomenon of great interest both for researchers and practitioners. Although intra‐team interaction is well supported by established agile practices, the critical interaction between the agile team and other parts of the organization is still unexplored in literature. Such interactions slow down the development, hindering the achievement of business goals based on speed: short time to market, quick replication of products of a product‐line, and reaction time for product evolution. We have employed a two‐year long multiple‐case case‐study, collecting data through interviews and a survey in three large companies developing embedded software. Through a combination of qualitative and quantitative analysis, we have found strong evidence that interaction challenges between the development team and other groups in the organization hinder speed and are widespread in the organizations. This paper also identifies current practices in use at the studied companies and provides detailed guidelines for novel solutions in the investigated domain. Such practices are called boundary‐spanning activities in information system research and coordination theory. We present a comparison between large embedded software companies employing agile and developing a line of products based on reused assets and agile companies developing pure software. We highlight specific contextual factors and areas where novel spanning activities are needed for mitigating the interaction challenges hindering speed. Copyright © 2015 John Wiley & Sons, Ltd.